Lucy Hooper, William Blake, and “The Fairy’s Funeral” - Linkin, Harriet (Romanticism and Victorianism on the Net, 2009)
AbstractThe American poetess and abolitionist Lucy Hooper (1816-1841) was the first North American to publish a poem inspired by Blake’s prophetic imagination, “The Fairy’s Funeral” (1833), which transforms the famous anecdote about Blake witnessing a fairy funeral into a visionary lyric. This essay provides a brief introduction to Hooper, perhaps best-known as the subject of Whittier’s elegy “On the Death of Lucy Hooper” (1841), situates her in a literary milieu of British Romantic poets that includes Hemans, Landon, Byron and Clare, discusses how an American poetess from Brooklyn might have learned about Blake and his work, and reads “The Fairy’s Funeral” as a critique of Blake’s often violent representation of fairies and flowers.